CD39 positive regulatory T cell frequency as a biomarker of treatment response to methotrexate in rheumatoid arthritis. (26th August 2018) - Gupta, Vikas; Katiyar, Shobhita; Singh, Ankita; Misra, Ramnath; Aggarwal, Amita
Abstract: Aim: Nearly one‐third of patients with rheumatoid arthritis (RA) do not respond to Methotrexate (MTX), the first‐line therapy in RA. CD39, an ectonucleotidase highly expressed on regulatory T cells (Tregs), is responsible for production of adenosine, an important anti‐inflammatory mediator of MTX action. Higher expression of CD39 on Tregs improves their suppressive capacity. Therefore, we aimed to study the role of CD39 + Treg frequency as a biomarker for MTX treatment response in RA. Methods: Patients with active RA who were naive to disease‐modifying anti‐rheumatic drugs were enrolled. Frequencies of CD39 + Tregs (CD4 + CD25 + FoxP3 + CD39 + cells) and CD4 + CD25 + CD39 + cells were determined by flow cytometry in peripheral blood before the start of therapy. After 4 months of MTX monotherapy, patients were classified into responders (European League Against Rheumatism [EULAR] good/moderate response) and non‐responders (EULAR no response). All samples were genotyped for single nucleotide polymorphisms (SNPs) rs11188513 and rs7071836 in the ENTPD1 (CD39) gene. Results: After 4 months of MTX monotherapy, 54 patients were classified as responders and 16 as non‐responders. The baseline CD39 + Treg and CD4 + CD25 + CD39 + cell frequencies were significantly higher in the responder group as compared with the non‐responder group ( P < 0.05 and P < 0.01, respectively). AA genotype at SNP rs7071836 was associated with poor response to MTX ( P < 0.05; odds ratio = 5.67; 95% CI = 1.12–28.75). Conclusion: Higher frequencies of CD39 + Tregs and CD4 + CD25 + CD39 + cells in the peripheral blood are associated with response to MTX in RA and hence, these could be considered as potential biomarkers for prediction of response to MTX treatment.